Predicting 3D Structure, Cross Talks, and Prognostic Significance of KLF9 in Cervical Cancer - Safi, Sadia; Badshah, Yasmin; Shabbir, Maria; Zahra, Kainat; Khan, Khushbukhat; Dilshad, Erum; Afsar, Tayyaba; Almajwal, Ali; Alruwaili, Nawaf W.; Al-disi, Dara; Abulmeaty, Mahmoud; Razak, Suhail (Frontiers in Oncology, 2022)
Our study aimed to identify the new blood-based biomarkers for the diagnosis and prognosis of cervical cancer. Moreover, the three-dimensional (3D) structure of the KLF9 was also determined in order to better understand its function, and a signaling pathway was constructed to identity its upstream and downstream targets. In the current study co-expression of Tumor Protein D52 (TPD52), Krueppel-like factor9 (KLF9), micro-RNA 223 (miRNA 223), and Protein Kinase C epsilon (PKCε) was evaluated in cervical cancer patients and a possible relation with disease outcome was revealed. The expression of TPD52, KLF9, miR-223, and PKCε was studied in the blood of 100 cervical cancer patients and 100 healthy controls using real-time PCR. The three-Dimensional structure of KLF9 was determined through homology modeling via the Swiss model and assessed by the Ramachandran plot. The predicted three-dimensional structure of KLF9 had a similarity index of 62% with its template (KLF4) with no bad bonds in it. In order to construct a genetic pathway, depicting crosstalk between understudied genes, String analysis, KEGG, and DAVID software were used. The constructed genetic pathway showed that all the understudied genes are linked with each other and involved in PI3K/Akt Signaling Pathway. There was a 23-fold increase in TPD52 expression, 2-fold increase in miR-223 expression, 0.14-fold decrease in KLF9 expression, and 0.05-fold decrease in PKCε expression in cervical cancer. In the present study, we observed an association of TPD52, KLF9, miR-223, and PKCε expression with tumor stage, metastasis, and treatment status of cervical cancer patients. The elevated expression of TPD52, miR-223, and reduced expression of KLF9 and PKCε in peripheral blood of cervical cancer patients may serve as a predictor of disease diagnosis and prognosis. Nevertheless, further in-vitro and tissue level studies are required to strengthen their role as potential diagnostic and prognostic biomarkers.